2018
DOI: 10.1111/evo.13597
|View full text |Cite
|
Sign up to set email alerts
|

Selection for pollen competitive ability in mixed-mating systems

Abstract: Coexpression of genes in plant sporophytes and gametophytes allows correlated gametic and sporophytic selection. Theory predicts that, under outcrossing, an allele conferring greater pollen competitive ability should fix within a population unless antagonistic pleiotropy with the sporophyte stage is strong. However, under strong selfing, pollen competitiveness is immaterial as superior and inferior competitors are deposited on opposite stigmas, producing assortative competition. Because many plant species have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…Haploid gene expression in pollen means that selfers may nevertheless experience pollen competition as an extra source of selection against new deleterious mutations on top of selection in sporophytes (Dapper & Wade, ). Specifically, pollen competition in predominant selfers may disfavour low‐quality self‐pollen harbouring deleterious alleles that might otherwise exacerbate inbreeding depression or deleterious mutation accumulation (in the absence of antagonistic effects between gametophyte and sporophyte) (Peters & Weis, ); but see (Damgaard et al ., ). This idea also is related to the ‘selection‐arena hypothesis’ (Stearns, ), and its effectiveness might be limited by low pollen production within a selfing flower.…”
Section: ‘Syndromes’ Of Reproductive Modementioning
confidence: 99%
“…Haploid gene expression in pollen means that selfers may nevertheless experience pollen competition as an extra source of selection against new deleterious mutations on top of selection in sporophytes (Dapper & Wade, ). Specifically, pollen competition in predominant selfers may disfavour low‐quality self‐pollen harbouring deleterious alleles that might otherwise exacerbate inbreeding depression or deleterious mutation accumulation (in the absence of antagonistic effects between gametophyte and sporophyte) (Peters & Weis, ); but see (Damgaard et al ., ). This idea also is related to the ‘selection‐arena hypothesis’ (Stearns, ), and its effectiveness might be limited by low pollen production within a selfing flower.…”
Section: ‘Syndromes’ Of Reproductive Modementioning
confidence: 99%
“…2012). Equation (26) shows that selfing reduces haploid selection by two (σ/2 term) because male haploid selection is ineffective under selfing and female haploid selection is unchanged (see also Peters and Weis 2018, for more specific selection schemes).…”
Section: Resultsmentioning
confidence: 99%
“…NA = not applicable. References—1 = Hayman (1953); 2 = Weir (1970); 3 = Kimura and Ohta (1971); 4 = Rocheleau and Lessard (2000); 5 = Hedrick (1998); 6 = Jordan and Connallon (2014); 7 = Tazzyman and Abbott (2015); 8 = Peters and Weis (2018); 9 = Glémin (2010); 10 = Fishman and Kelly (2015); 11 = Jain and Jain (1970); ts = this study (indicated when new results are provided, not only rederived); * = More precisely, the case studied in 8 is male haploid/sex‐independent diploid antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…Selective advantage of facilitativeness (costly to male) versus competitiveness (costly to female) may differ between the perspectives of paternal versus maternal plants (sexual conflict; Arnqvist & Rowe, ; Delph & Havens, ). Possible outcomes of such conflicts can be sensitive to the degree of self‐fertilization, as suggested in both empirical (Brandvain & Haig, ; Cailleau, Grimanelli, Blanchet, Cheptou, & Lenormand, ; Raunsgard et al, ) and theoretical studies (Jordan & Connallon, ; Peters & Weis, ). Especially in the context of intersexual interactions in spatially subdivided plant populations, I would propose that the interplay between the reproductive system (or mating system) and sexual conflict are of critical importance, although these are relatively unexplored in previous studies.…”
Section: Discussionmentioning
confidence: 97%